Serum suPAR levels are modulated by immunosuppressive therapy of minimal change nephrotic syndrome - Gellermann, Jutta; Schaefer, Franz; Querfeld, Uwe (Pediatric nephrology, 2014)
Soluble urokinase-type plasminogen activator receptor (suPAR) could be a causative factor in idiopathic focal segmental glomerulosclerosis (FSGS). It is currently unknown to what extent suPAR levels could be affected by treatment with immunosuppressive drugs such as cyclosporin A (CsA) and mycophenolate mofetil (MMF). Treatment with CsA, but not MMF, is accompanied by nephrotoxicity, and since suPAR levels correlate with glomerular filtration rate (GFR), treatment with these drugs could indirectly modulate suPAR levels by their effect on renal function.